1979
DOI: 10.1017/s0022172400025626
|View full text |Cite
|
Sign up to set email alerts
|

The development and assessment of a bacteriocin typing method forKlebsiella

Abstract: SUMMARYKlebsiellas are generally typed by the method of capsular serotyping but, although this is a reliable method, it is time consuming, requires the production of a large number of antisera and is not generally available. For this reason another method for typing klebsiellas was sought.A bacteriocin typing method involving mitomycin C induction was developed and the cultural conditions giving optimum klebecin production and the best methods of testing the sensitivity of the organisms to klebecins were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The clustering patterns are included for comparison in Table 4. (Edmondson & Cooke, 1979;Hardy, 1982;Simoons-Smit et al 1983). Since only a minority of strains of C. perfringens is bacteriocinogenic, a passive typing method is of more value as long as the variability of typing patterns can be assessed.…”
Section: Examination Of Unrelated Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The clustering patterns are included for comparison in Table 4. (Edmondson & Cooke, 1979;Hardy, 1982;Simoons-Smit et al 1983). Since only a minority of strains of C. perfringens is bacteriocinogenic, a passive typing method is of more value as long as the variability of typing patterns can be assessed.…”
Section: Examination Of Unrelated Isolatesmentioning
confidence: 99%
“…By multiple typing of strains of klebsiella, Edmondson & Cooke (1979) showed that only 670 reproducibility could be expected if patterns differing by one reaction were regarded as distinct. Anderhub et al (1977), studying clinically related strains of Serratia marcescens, found that 520% and 730 of 89 cultures gave identical typing results on two occasions by cross-streaking and mitomycin-induction methods respectively.…”
Section: Examination Of Unrelated Isolatesmentioning
confidence: 99%
“…Gentamicin-resistant klebsiella of serotype K2 were also received from other hospitals both in and out of the London area. Klebecin typing was as described by Edmondson & Cooke (1979) using klebecinproducer and indicator strains provided by Professor E. M. Cooke. Sensitivity testing was as described by Datta et at.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…The strains that were accepted as klebsiellas had the following characters (see Edmondson and Cooke, 1979): non-motile, acid produced from inositol, hydrogen sulphide not produced (Donovan, 1966), acid produced from adonitol, urea hydrolysed, no ornithine decarboxylase.…”
Section: Sources Of Strains Examinedmentioning
confidence: 99%